Tingkat Kepuasan Konsumen Sayuran Organik di Jumbo Pasar Swalayan Manado - Fiskarina, Eva; Sendow, Martha Mareyke; Baroleh, Jenny (Sam Ratulangi University, 2023)
This study aims to determine the level of consumer satisfaction of organic vegetables at Jumbo Supermarket Manado. This research was conducted from May 2022 to October 2022. This study uses two types of data, namely primary and secondary data. The method used in sampling is the non-probability sampling technique where the collection of information and knowledge from respondents uses the accidental sampling method. Respondents in this study were consumers who had made a purchase and were willing to be interviewed as many as 30 respondents. The data were analyzed using Likert scale measurements. The results showed that the level of consumer satisfaction of organic vegetables at the Jumbo Supermarket in Manado was categorized as very satisfied, based on the results of the study with an index of 87.29%. Consumers are very satisfied with the price and availability of organic vegetables, freshness (physical appearance of vegetables), place, and quality of service at Jumbo Supermarkets.